PENGARUH CIRCUIT TRAINING TERHADAP PENINGKATAN KELINCAHAN DAN KAPASITAS VITAL PARU-PARU - Adi Merta Yoga, I Made (Universitas Pendidikan Ganesha, 2013)
This study aimed to determine the effect of circuit training on agility and the vital capacity of the lungs. This study was a quasi experiment study with nonrandomized pretest posttes control groups design. The subject of this study were 50 male participants of extracurricular football at SMP Negeri 4 Negara in academic year 2012/2013. Agility was measured by using dogging run, while the vital capacity of the lungs was measured by using spirometer and the data was analyzed by independent t-test with significance of (Î±) 0,05 by using SPPSS 16.0. The result of analysis data by using independent t-test showed that circuit training affected the improvement of agility and the vital capacity of the lungs with significance value for agility was 0.000 and 0.000 for the vital capacity of the lungs. From the result of analysis data could be concluded that circuit training affected the improvement of agility and the vital capacity of the lungs. It is suggested for the coach, teacher and athlete to use circuit training as one alternative in improving agility and the vital capacity of the lungs.